2014
DOI: 10.5539/ass.v10n11p149
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Board of Directors Characteristics, Audit Committee Characteristics and Executive Committee Characteristics on Firm Performance in Oman: An Empirical Study

Abstract: This study is an attempt to achieve the main objective by examining the association between the board of director's characteristics, audit committee characteristics and the executive committee characteristics and the performance of the Oman companies. This study used many assumptions to test the relationship between independent variables and dependent variable as discussed in the section explaining the study method. The data comprised of 162 non-financial companies because financial and non-financial companies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
32
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 126 publications
6
32
0
3
Order By: Relevance
“…As mentioned earlier, the attribute of AS has no or a lesser relationship with the performance during the investigated period. Our result may support Aldamen et al (2011), Yahya et al (2012, Ebrahim (2014). However, we should note that the absolute size of the audit committee was still too small during the period (see Table 6).…”
Section: Discussionsupporting
confidence: 83%
“…As mentioned earlier, the attribute of AS has no or a lesser relationship with the performance during the investigated period. Our result may support Aldamen et al (2011), Yahya et al (2012, Ebrahim (2014). However, we should note that the absolute size of the audit committee was still too small during the period (see Table 6).…”
Section: Discussionsupporting
confidence: 83%
“…Beside financial fairness of a corporation it also enhances the financial and managerial capabilities by insuring the implementation of good practices (Epps & Cereola, 2008). Other studies like Anderson, Mansi and Reeb (2004), Matar et al (2014) show the same positive association between firm value and audit committee. To reduce the agency problems it is very important to place a well functioning and an independent audit committee (Erickson et al, 2005).…”
Section: Audit Committeementioning
confidence: 58%
“…In theory, firms should benefit from having larger boards for monitoring, strategy formulation and access to resources leading to improved financial performance. Empirical studies by Almatari et al (2014b) and Johl et al (2015) demonstrated a significant positive relationship between board size and firm financial performance in Oman and Malaysia respectively. Other studies such as Rouf (2011) in Banagladesh and Ghabayen (2012) in the Kingdom of Saudi Arabia (KSA) did not identify any significant relationship.…”
Section: Board Sizementioning
confidence: 99%
“…According to Khalifa (2018), independent members of the audit committee play an important role in improving the monitoring of management which can lead to improved firm financial performance. Empirical studies by Yasser et al (2011) and Almatari et al (2014b) in Pakistan and Oman respectively showed that there was a significant positive relationship between independent members of the audit committee and firm financial performance. However, empirical studies from Ghabayen (2012) and Kajola (2008) in KSA and Nigeria respectively identified no significant relationship.…”
Section: Audit Committee Independent Membersmentioning
confidence: 99%
See 1 more Smart Citation